THE TRANSNATIONAL FAMILY, CONFLICT OF LAWS BETWEEN ISLAMIC AND EUROPEAN SYSTEM - Monica Di Monte (European Scientific Journal, ESJ, 2014)
The goal that animates the present work is to analyze, on the basis of the rules of private international law, the question of the right bed where one of the parties, or both, are devoted to Islam. Such devotion tends to imply, observant, a perfect coincidence between the legal sphere and the religious sphere. Which is why the phenomenon of migration, by Muslims as it poses many problems with respect to the applicable law. The focus, in the remainder of this paper, it invests the Islamic family law and, specifically, the types of family ties outside our legislation involving conflicts of civilization. The intent is to understand how posing as the Italian domestic law when, following the provisions of private international law, it’s "in touch" with the rules and practices of the Islamic family law that may conflicts with the fundamental principles of the law of the forum whose interest is in the exception of public order. The Islamic system is in fact incompatible with fundamental principles of our legal system (and not just legal): first the secular state and religious pluralism.